CASE REPORT ON MOCHARASA (HAEMOSTYPTIC DRUG)- ACTION AND USES - Verma, *Sarita; Singh, D.C.; Singh, Rajeev; Nautiyal, Rakhi (International Journal of Ayurveda and Pharma Research, 2017)
Medicinal plants are resources of newer drug evolution and form the basis of all alternative medicine system. Mocharasa-reddish brown colored secondary metabolite in the form of exudate from Silk - Cotton Tree (Salmali malabarica) and is in demand in pharmaceutical industries for preparation of formulations used for bleeding disorders. Mochrasa is one of source for the life saving drug and known by synonyms like â€œNiryasa, Pichha, Pichhalsaar, Salmaliveshtaka, Mochsrava, Mochsaar denoting its sticky characteristic. Their therapeutic uses are well described in Ayurvedic, Unani and Siddha literature in various bleeding disorders like menorragia, haemptysis, bloody dysentery, diarrhoea mainly. It has good potential of cooling, demulscent, haemostyptic and astringent nature. Due to its binding nature used to heal wounds, ulcers, inflammation and in skin disorders. It is well known for aphrodiasic action in traditional practices as well. It is mild in nature and can be used in pregnant women and children. In Shodhana process of Panchkarma, it is main content of â€œ Pichha basti â€ which is given per rectal route which proves its mild astringent and styptic action. Main chemical constituents are L-arbanose, gallic acid, tannic acid with other alkaloids. Various formulations containing Mochrasa are Sunisnaak Changeri Ghrita, Bilwaadi churna, Kutajastak avhleha, Sammangaadi Churna, Changeri Ghrita etc. Various newer trials for antioxidant, analgesic, hepatoprotective action etc. are going on the basis of properties to revalidate the ancient knowledge. Here is an attempt to through light on collection process, purification and availability of raw drug as well extracts in market by collecting data from various sources on every aspect of Mocharasa and their therapeutic and folklore uses.